DINAMIKA DERAJAT PERSAINGAN INDUSTRI PERBANKAN INDONESIA - Zuhroh, Idah (Journal of Innovation in Business and Economics, 2014)
This study aims to investigate the dynamics of the degree of competition in the banking industry in Indonesia, especially in the banking consolidation period ( 2000 -2008)  is measured from the concentration ratio (CR 8) and Learner index. Samples were grouped into eight largest bank size (CR8) and outside CR8. The findings indicate that during the consolidation period (2000 -2006), concentration ratio tend to decrease  of 70% towards 62%. But after  periode 2006, concentration index is  constan. Degree of competition   by largest  bank size  (CR8)  indicated by an Learner  index greater and is likely to increase rather than smaller  bank size  (outside CR 8). This gives a signal that  largest bank size  have more market power to direct output prices  ( credit ) above marginal cost  compared to the group of banks outside of CR 8.